Persaingan Pasar dan Tantangan Industri Farmasi Halal di Indonesia - Sunarmo, Sunarmo; Arsyad, Aisyah Tiar; Widuhung, Sisca Debyola (Penerbit Goodwood, 2025)
Purpose: This research aims to ascertain the degree of competitiveness and obstacles faced by the Indonesia Stock Exchange-listed halal pharmaceutical sector between 2012 and 2022 Methodology: This study consists of quantitative and qualitative data sources from the financial reports of 10 halal pharmaceutical companies listed on the Indonesia Stock Exchange in 2022, as well as a literature review of the halal pharmaceutical industry. The data collection and analysis technique uses panel data with the Panzar and Roose market competition model approach and a secondary data approach based on a literature review. Results: Based on research testing, two results were obtained. The first is from the Panzar and Roose models, showing that the halal pharmaceutical industry in Indonesia from 2012 to 2021 was in non-equilibrium and competed in a monopolistic market. The results indicate that pharmaceutical companies use non-price tactics and policies to remain in business. Second, the literature review found that the halal pharmaceutical industry has the potential to increase growth due to the increasing public interest in buying halal products and the existence of mandatory halal regulations under the Halal Product Assurance Organizing Agency (BPJPH) Law. Conclusion: However, there are obstacles and challenges faced in the development of the halal pharmaceutical industry, such as the limitations of halal-certified medicines, supply chains, raw materials still being imported, and the quality of human resources Limitations: The limitation of this study is that it only uses financial ratio data including solvency ratios, activities and profitability ratios in 10 pharmaceutical companies and scientific articles about the halal industry. The research does not involve halal pharmaceutical industry players with a direct interview approach. Contribution: This research is useful for pharmaceutical industry players looking at competition between companies, especially increasing competition instead of price and innovation. It is necessary for the government to implement massive policies in terms of both business supervision and halal products.